Enhanced photocatalytic activity of TiO2/UiO-67 under visible-light for aflatoxin B1 degradation. Issue 11 (25th February 2022) - Zhang, Jia; Gao, Xintong; Guo, Wenbo; Wu, Zengnan; Yin, Yilin; Li, Zenghe
Abstract : Enhanced photocatalytic activity of TiO2 /UiO-67 under visible-light for aflatoxin B1 degradation. Abstract : TiO2 has great potential in photocatalytic degradation of organic pollutants, but poor visible light response and low separation efficiency of photogenerated electron–hole pairs limit its wide applications. In this study, we have successfully prepared TiO2 /UiO-67 photocatalyst through an in situ solvothermal method. The degradation rate of aflatoxin B1 (AFB1) is 98.9% in only 80 min, which is superior to the commercial P25, commercial TiO2 and most of reported photocatalysts under visible light irradiation. In addition, the TiO2 /UiO-67 photocatalyst showed excellent recyclability. We demonstrated that the enhanced photocatalytic mechanism was owing to the heterojunction between TiO2 and UiO-67, which enhanced effectively the separation photogenerated charge carriers and visible light response. The free radical trapping tests demonstrated that superoxide radicals (˙O2 − ), holes (h + ) and hydroxyl radicals (˙OH) were the main active species and then oxidized AFB1 to some small molecules.